Influence of growth stage and season on the antioxidant constituents of Cosmos caudatus - Mediani, Ahmed; Abas, Faridah; Tan, Chin Ping; Khatib, Alfi; Lajis, Nordin H. (Springer US, 2012)
The impact of tropical seasons (dry and wet) and growth stages (8, 10 and 12 weeks) of Cosmos caudatus on the antioxidant activity (AA), total phenolic content (TPC) as well as the level of bioactive compounds were evaluated using high performance liquid chromatography (HPLC). The plant morphology (plant height) also showed variation between the two seasons. Samples planted from June to August (during the dry season) exhibited a remarkably higher bioactivity and height than those planted from October to December (during the wet season). The samples that were harvested at eight weeks of age during the dry season showed the highest bioactivity with values of 26.04 g GAE/100 g and 22.1 μg/ml for TPC and IC50, respectively. Identification of phytochemical constituents in the C. caudatus extract was carried out by liquid chromatography coupled with diode array detection and electrospray tandem mass (LC-DAD-ESIMS/MS) technique and the confirmation of constituents was achieved by comparison with literature data and/or co-chromatography with authentic standards. Six compounds were indentified including quercetin 3-O-rhamnoside, quercetin 3-O-glucoside, rutin,quercetin 3-O-arabinofuranoside, quercetin 3-O-galactoside and chlorogenic acid. Their concentrations showed significant variance among the 8, 10 and 12-week-old herbs during both seasons.